Synthesis of Zeolite ZSM-5 from Biosilica of Diatom Nitzschia closterium without Structure Directing Agent - Tria, Ade
ZSM-5 is a crystalline aluminosilicate with high silica/alumina ratio and widely applied as a catalyst in the petrochemical industry. Commercial silica and organic template commonly called as SDA (structure directing agent) are precursors that generally used in zeolite synthesis. To reduce the cost of synthesis, the commercial silica source can be replaced with natural silica, such as biosilica of diatom Nitzschia closterium. Moreover, the use of SDA can be eliminated from ZSM-5 synthesis. Therefore, the aim of this study is to synthesize ZSM-5 from biosilica of diatom N. closterium without SDA with hydrothermal method. The steps of the present research included the cultivation of diatom N. closterium cells, isolation of biosilica by using 65% (w/w) HNO3 and calcining, synthesis of ZSM-5 from biosilica of N. closterium, and characterization by the methods of infrared spectroscopy (FT-IR), scanning electron microscope energy dispersive X-ray spectroscopy (SEM-EDX), and X-ray diffraction (XRD). The results showed that the density of diatom N. closterium cells harvested at 8th d was 6.15 ± 0.53 × 106 cell/mL with biomass density of 2.05 ± 0.11 g/L. Inorganic compound products (42% (w/w)) were obatained from biomass heated over 600 °C. Morphology of biosilica was pennate and had nanopores with size of 40–750 nm. EDX result showed that N. closterium biosilica contained 42.5% silicon and 57.5% oxygen. Siloxan groups (Si–O–Si) of N. closterium biosilica were identified at 806.25 dan 1093.64 cm–1. N. closterium biosilica showed amorf. Meanwhile, difractogram of ZSM-5 synthesized from N. closterium biosilica had similar diffraction pattern with standard of ZSM-5 indicating ZSM-5 successfully synthesized. Morphology of ZSM-5 synthesized was fragmen-like N. closterium biosilica with maintaining the structure of nanopore. In addition, other morphological structure of N. closterium biosilica in the form of spherical with diameter of ~8 ?m was observed.